2002
DOI: 10.1093/geronb/57.4.p358
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Death in Older Adults: Predictions From Terror Management Theory

Abstract: Terror management theory asserts that death fear (fear of annihilation) is buffered by self-esteem and beliefs in literal and symbolic immortality achieved through participation in the cultural system. The aims of this study were to determine how variables suggested by the theory were related to fear of death measures. Participants were 123 Black and 265 White elders aged 60 to 100 years; they were assessed on the Multidimensional Fear of Death Scale (MFODS), self-esteem, religiosity, locus of control, socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
107
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 32 publications
9
107
4
3
Order By: Relevance
“…People may not be consciously aware of their fear and anxiety of death until they are confronted with the prospect of their own mortality. Thus, it may be easier for a person to report less death fear when one is relatively healthy (Cicirelli, 2002). This points to another reason for future research to make efforts in sampling older adults that reside in nursing home or hospice programs.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%
“…People may not be consciously aware of their fear and anxiety of death until they are confronted with the prospect of their own mortality. Thus, it may be easier for a person to report less death fear when one is relatively healthy (Cicirelli, 2002). This points to another reason for future research to make efforts in sampling older adults that reside in nursing home or hospice programs.…”
Section: Study Limitations and Future Researchmentioning
confidence: 99%
“…Although the term death anxiety might appear to be self-explanatory, with the implicit assumption that it is a unidimensional construct, Cicirelli's (2002) research, using the Multidimensional Fear of Death Anxiety (MFOD) scale developed by Hoelter (1979), suggested that death anxiety is in fact multidimensional (see also Florian & Kravetz, 1983). The MFOD contains eight subscales: Fear of Being Destroyed (e.g., ''I do not like the thought of being cremated''); Fear of Premature Death (e.g., ''I am afraid I will not have time to experience everything I want to'' ); Fear of Conscious Death (e.g., ''I hope more than one doctor examines me before I am pronounced dead''); Fear of the Unknown (e.g., ''I am afraid that death is the end of one's existence''); Fear of the Dying Process (e.g., ''I am afraid of experiencing a great deal of pain when I die''); Fear of the Dead (e.g., ''Discovering a dead body would be a horrifying experience''); Fear for Significant Others (e.g., ''Since everyone dies, I won't be too upset when my friends die''; reverse-coded); and Fear of the Body after Death (e.g., ''The thought of my body decaying after I die scares me'').…”
mentioning
confidence: 99%
“…After Cicirelli's (2002) elderly (M age ¼ 73 years) participants completed the MFOD (among other measures), a principal component analysis of the eight subscales revealed two components of death anxiety: unknown death anxiety and known death anxiety. Cicirelli defined unknown death anxiety as ''the fear of annihilation, the core fear of TMT'' (p. 361), and it contained the Fear of the Unknown subscale only.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Spirituality and religion for elderly African Americans are clearly about living and coping and not about preparing for the hereafter (Cicirelli 2002;Krause 2002Krause , 2003.…”
Section: Introductionmentioning
confidence: 99%